Endocrinopathies in Adult Egyptian Thalassemia Patients, A Cross Section Study - El-Salakawy, Walaa Ali; Wahed Hassan, Essam Abdel; Mohamed Said, Rasha Magdy; Saeed Ahmed, Alia Mohammed; moniem Radwan, Rania Abdel; Hussien Abdalla, Nour Elhoda (QJM : An International Journal of Medicine, 2024)
background Endocrine abnormalities are the most common complications of transfusion dependent thalassemias (TDT). Although the prevalence of endocrinopathies is less in nontransfusion dependent thalassemias (NTDT), they are still encountered, especially with advancing age. This necessitates regular screening. Evaluation and treatment of endocrinological disorders are the same as that of transfusion dependent patients. Aim is to asses the common endocrinal disorders in patients with thalassemia; TDT and NTDT for early detection and replacement therapy. Subjects and Methods This study is across sectional study, it included 100 patients with thalassaemia; 50 patients who were (TDT) and 50 patients who were (NTDT). Patients who are ≥ 18 years old, with thalassemia major TM and thalassemia intermedia TI, Patients with or without splenectomy, Transfusion dependent and non-transfusion dependent patients, all were included in the study. Results Study showed that there is a statistically significant positive correlation between serum ferritin and thyroid stimulating hormone(TSH) and there is negative correlation with Sex Hormons, S.Cortisol, GH level. Also there is negative correlation between (Sex Hormons, S.Cortisol, Growth hormone GH) and frequency of transfusion. Study shows that Validity of serum ferritin at cutoff point more than 1100 for prediction of patients who are transfusion dependent.in terms of sensitivity was 100% and specificity was 90%. Conclusion thalassemia’s patients are still suffering from many endocrine disorders, and This necessitates early regular screening, as Early identification of endocrinal disorders and use of iron chelation reverse this disorders.